DIPLOMASI PUBLIK JEPANG DALAM UPAYA PEMULIHAN CITRA MAKANAN JEPANG (2011-2019) - Sabrina Az Zahra (2022)
Public diplomacy is one of the instruments which is often used by the state to achieve its interests, including in image restoration. This study aims to analyze Japan's public diplomacy in an effort to restore the image of Japanese food after the Fukushima nuclear power plant accident in March 2011 in which it has caused radioactive contamination in various aspects of the Japanese environment, including the food, which then led to fear and speculation circulating in the domestic and international community regarding Japanese food safety. To find out the public diplomacy carried out by Japan in restoring its food image, this study uses the theoretical framework of Public Diplomacy, Gastrodiplomacy, and Soft Power. The author uses a qualitative method where in this study the author will provide an explanation of Japan's public diplomacy in an effort to restore its food image seen from the three dimensions of Mark Leonard's Public Diplomacy which includes news management, strategic communication, and relationship building using primary and secondary data obtained through interviews as well as data analysis. The three dimensions of public diplomacy have helped the Japanese government in improving the image of Japanese food, however, there are two dimensions that stand out the most in providing significant results for the restoration of the image of Japanese food, namely the dimensions of strategic communication and relationship building. Keywords: Public diplomacy, food safety, Fukushima nuclear power plant accident, image restoration